1983
DOI: 10.1038/bjc.1983.230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzymic removal of cell surface constituents on metastatic colonisation potential of mouse mammary tumour cells

Abstract: Clinical observations indicate that individual tumours vary in the extent to which they colonise distant organs and in the distribution of their metastatic deposits after blood-borne dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The observations are supported by those published earlier (Sargent et al, 1983) demonstrating that vigorous digestion of surface components by various enzymes did not have striking effects on colonisation capability by similar murine mammary tumour cells. In the current work the most marked effect on pulmonary Irimura and Nicolson (1982).…”
Section: Discussionsupporting
confidence: 81%
“…The observations are supported by those published earlier (Sargent et al, 1983) demonstrating that vigorous digestion of surface components by various enzymes did not have striking effects on colonisation capability by similar murine mammary tumour cells. In the current work the most marked effect on pulmonary Irimura and Nicolson (1982).…”
Section: Discussionsupporting
confidence: 81%
“…Experimental induction of MHC molecules in some tumour cell lines lacking in these determinants has demonstrated the involvement of immune phenomena in modulating metastatic spread (Hui et al, 1984;Wallich et al, 1985). Other cell surface molecular differences between metastatic and nonmetastatic tumour variants are thought to affect cell-cell and cell-tissue interactions influencing adhesiveness and organ colonising properties of tumour cells (Reiber & Reiber, 1981;Sargent et al, 1983). Non-specific defence mechanisms have also been shown to control tumour cell dissemination (Barlozzari et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative differences in terminal cell surface carbohydrates (Fogl et al, 1983), altered cell surface protein composition after enzyme treatment (Sargent et al, 1983) and differences in glycoprotein expression (Altevogt et al, 1982) have all been shown to contribute to the metastatic capacity of different tumour cell lines. The most notable finding to date is an inverse correlation between metastatic potential and the expression of major histocompatibility complex (MHC) molecules (Wallich et al, 1985;Hui et al, 1984;Albino et al, 1981;Natali et al, 1983).…”
mentioning
confidence: 99%
“…In addition, preclinical data obtained in cell culture (Liu et al 1987;Kohno et al 1988;Scheithauer et al 1988;Lehnert et al 1989) and experimental rodent tumour models (Seipelt and Kohlheb 1967;Pawlowski et al 1979;Sargent et al 1983) are scanty and inconsistent.…”
Section: Introductionmentioning
confidence: 99%